Effects of extracellular proteome on wheat straw pretreatment during solid-state fermentation of Phlebia radiata ATCC 64658. (April 2016) - Bule, Mahesh Vitthal; Chaudhary, Innu; Gao, Allan Haiming; Chen, Shulin
Abstract: Biological pretreatment of lignocellulosic biomass potentially offers a less energy intensive alternative to chemical pretreatment for the reduction of recalcitrance towards cellulolytic enzymes, but possesses some disadvantages, including a slow rate and loss of polysaccharides. This study characterizes the biodegradation of wheat straw by Phlebia radiata, a white rot fungus capable of secreting three major classes of ligninolytic enzymes: lignin peroxidase, manganese peroxidase, and laccase under natural conditions. We investigated the correlation between synergistic action of fungal enzymes and characteristics of the pretreated biomass. The results showed a sequential expression of enzymes over the course of a three-week pretreatment, with members of the peroxidase family being expressed in week one, followed by laccase expression starting in week two which continued until the course of pretreatment. This highlights the synergy of ligninolytic enzymes in the selective degradation pattern for wheat straw. 1 H– 13 C HSQC NMR spectroscopy results demonstrated reduced amounts of syringyl (S) and hydroxyphenyl (H) lignin after pretreatment. Moreover, the reduction in H lignin was also seen in Pyrolysis – GC/MS and FT-IR results. This strongly suggests that this unique lignin modification pattern is associated with P. radiata extracellular proteome, as expressed during the solid-state fermentation (pretreatment) of wheat straw. Graphical abstract: Highlights: Ligninolytic enzymes of Phlebia radiata work synergistically in wheat straw degradation. MnP is secreted early in the process, to generate substrate for laccases. Laccase allows the lignin modification to continue via relatively higher breakdown of H-units than G and S subunits. Sequential secretion strategy serves the purpose of an efficient biodegradation.